Agonistic anti‐human Fas monoclonal antibody induces fibroblast‐like synoviocyte apoptosis in haemophilic arthropathy: potential therapeutic implications. (20th November 2013) - Romano, E.; Manetti, M.; Peruzzi, F.; Melchiorre, D.; Milia, A. F.; Bellando‐Randone, S.; Nishioka, K.; Innocenti, M.; Carulli, C.; Linari, S.; Morfini, M.; Ibba‐Manneschi, L.; et al.
Summary Haemophilic arthropathy (HA) is characterized by chronic proliferative synovitis leading to cartilage destruction and shares some pathological features with rheumatoid arthritis (RA). Apoptosis has been implicated in RA pathogenesis, and an agonistic anti‐Fas monoclonal antibody (mAb) was found to induce RA fibroblast‐like synoviocyte (FLS) apoptosis and suppress synovial hyperplasia in animal models of RA. The aim of this study was to evaluate the effect of anti‐Fas mAb on HA‐FLS. FLS were isolated from knee synovial biopsies from six HA patients, six RA patients and six healthy subjects. The expression of Fas in synovial biopsies was investigated by immunohistochemistry. FLS were stimulated with anti‐Fas mAb at different concentrations, alone or in combination with tumour necrosis factor‐α (TNF‐α) and basic fibroblast growth factor (bFGF). Fas expression in FLS was assessed by Western blot. Cell viability was studied with the WST‐1 assay. Active caspase‐3 levels were measured using ELISA and Western blot. A strong Fas‐immunoreactivity was observed in different cells of HA synovium, including FLS, inflammatory cells and endothelial cells. Fas antigen was constitutively overexpressed in cultured HA‐FLS. Anti‐Fas mAb had a significant cytotoxicity on HA‐FLS in a dose‐dependent manner, either alone or in combination with TNF‐α and bFGF. These cytotoxic effects were due to the ability of anti‐Fas to induce HA‐FLS apoptosis, as shown by the increased active caspase‐3 levels. Anti‐Fas mAb exhibited a more pronounced pro‐apoptotic effect on HA‐FLS than RA‐FLS. Fas antigen is highly expressed on HA‐FLS and its stimulation by anti‐Fas mAb may be an effective strategy to induce HA‐FLS apoptosis.